Hubungan Daya Ledak Tungkai dan Keseimbangan Terhadap Kemampuan Lompat Jauh Siswa SDN 64 Medde - H. Hamkah (PINISI :Journal of Teacher Professional, 2020)
This research aims at finding out: (1) the correlation of explosive leg power and students' long jump ability; (2) the correlation of balance and students' long jump ability; (3) the correlation of explosive leg power and balance simultaneously towards the long jump ability of students. The population of this research was the entire students of SDN 64 Medde. The sample used was 30 male students which was choosen by simple random sampling. The data analysis technique used was descriptive analysis, correlation analysis and regression analysis at a significant level α = 0.05 through SPSS 21 version. The results of the research showed that: (1) there was a significant correlation of explosive leg power towards the long jump ability of students with the value 0.873 (ρ <α = 0.05); (2) there was a significant correlation of balance towards the long jump ability with the value of r test = 0.805 (ρ <α = 0.05); (3) there was a significant correlation of explosive leg power and balance toward the long jump ability of students with r test = 0.923 (ρ <α = 0.05).